Fluid and diet patterns associated with weight cycling and changes in body composition assessed by continuous monitoring throughout a college wrestling season - Lingor, R. J.; Olson, A. (The Journal of Strength and Conditioning Research, 2010)
This study examined the methods used to meet certification weight for wrestling and to measure the changes in body composition during 1 season for Division III college wrestlers. Nine college wrestlers completed this study. Body composition was analyzed by underwater weighing (UWW) and multifrequency bioelectrical impedance before and throughout the competitive season. Hydration status was measured by urine osmolality (Uosm) and urine specific gravity (Usg). Nutritional intake was measured for 2 1-week periods, once at the beginning and again near the end of the season. Subjects' fat-free mass (FFM) increased an average of 1.8 kg, whereas fat mass (FM) decreased 2.2 kg as indicated by UWW from the beginning to the end of the season. Wrestlers on average cycled their weight 3.4 kg (4.7% of body weight) per week. The majority of wrestlers cut weight by reducing calories and restricting fluids starting 2 days before the competition. Uosm and body weights on Friday suggested that for wrestlers to achieve the necessary weight loss by dehydration to "make weight" for a Saturday meet, wrestlers would approach a 5% level of dehydration. No loss of FFM because of weight cycling (WC) was evident to achieve competitive weight. Most wrestlers significantly restricted fluids and caloric intake in the 48 hours before weigh-in.